Science in a free society - Feyerabend, Paul (London Verso, 1987)
No study in the philosophy of science created such controversy in the seventies as Paul Feyerabends Against Method. In this work, Feyerabend reviews that controversy, and extends his critique beyond the problem of scientific rules and methods, to the social function and direction of science today.In the first part of the book, he launches a sustained and irreverent attack on the prestige of science in the West. The lofty authority of the expert claimed by scientists is, he argues, incompatible with any genuine democracy, and often merely serves to conceal entrenched prejudices and divided opinions with the scientific community itself. Feyerabend insists that these can and should be subjected to the arbitration of the lay population, whose closes interests they constantly affectas struggles over atomic energy programs so powerfully attest.Calling for far greater diversity in the content of education to facilitate democratic decisions over such issues, Feyerabend recounts the origin and development of his own ideassuccessively engaged by Brecht, Ehrenhaft, Popper, Mill and Lakatosin a spirited intellectual self-portrait.Science in a Free Society is a striking intervention into one of the most topical debates in contemporary culture and politics.